Collaborative optimization of the Mathews stability graph method and numerical simulation for the limit exposure area in stope - Chunlin You; Jianhua Hu; Jianing Li; Jiwei Zhang; Zhonghua Qi (Scientific Reports)
Abstract Significant hanging wall exposure in stopes of underground iron mines with inclined orebodies affects mine safety and efficiency. An extended Mathews stability graph method, combined with numerical simulations, was employed to evaluate stope stability. Rock mass quality was assessed using the RMR grading system and Q′ values. Stability probabilities were determined by fitting stability isoprobability lines on the Mathews stability graph and analyzing exposure time, along with FLAC3D modeling to analyze the mechanical response of different exposure areas. The results showed that the expanded Mathews stability graph could determine the stability probability of various exposure areas. Increasing the stope length under the same exposure area improved stress distribution and reduced plastic destruction. Reducing exposure time enhanced stope stability. Numerical simulations suggested optimal exposure areas and structural parameters: 30 m × 15 m and 40 m × 12.5 m, with a maximum exposure time of 3 months and corresponding limit exposure areas of 450 m2 and 500 m2, respectively. These findings effectively improved the stability and safety of the stopes.